A critical study of GST implementation and its effects on MSMES in the Indian Economy (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The Goods and Services Tax (GST), introduced in India in July 2017, represents one of the most significant indirect tax reforms aimed at simplifying the country’s complex tax structure and creating a unified national market. While the reform was expected to improve transparency and efficiency in the taxation system, its implementation has generated several challenges for Micro, Small, and Medium Enterprises (MSMEs). MSMEs play a vital role in the Indian economy by contributing significantly to employment generation, industrial production, and exports. However, due to limited financial resources, technological capabilities, and managerial expertise, these enterprises often struggle to adapt to large regulatory changes such as GST. The present study examines the challenges and negative impact of GST on MSMEs in India. The study is based on secondary data collected from government reports, research journals, official publications, and other credible sources. The findings indicate that GST has increased compliance requirements, created working capital constraints, and imposed technological and administrative burdens on small enterprises. MandaEconomytory digital filing systems, multiple return submissions, input tax credit dependencies, and procedural complexities have increased operational costs and administrative workload for MSMEs. Furthermore, the intensified market competition with large firms has placed additional pressure on small businesses struggling to meet compliance standards. The study concludes that although GST aims to improve tax transparency and economic integration, the transition has created several operational and financial difficulties for MSMEs, highlighting the need for simplified compliance procedures and supportive policy measures to protect the sustainability of small enterprises.